A Review of approaches in steviol glycosides synthesis - Samsulrizal, Nurul Hidayah; Noh, Abdul Latif; Meenakshi Sundram, Tamil Chelvan; Zainuddin, Zarina (International Society of Academicians, 2019)
Stevia rebaudiana (Bertoni) is a commercially important plant worldwide. The leaves of Stevia rebaudiana contain steviol glycosides which are non-caloric, high-potency sweeteners. They are suitable for substituting sucrose and other artificial sweetening agents. Stevia rebaudiana also has many different therapeutic uses, with antidiabetic, anti-cariogenic, antimicrobial, anticancer and antioxidative properties. Rebaudioside A and stevioside are the major glycosides produced in its leaves. However, development of new varieties of Stevia rebaudiana with a greater content of rebaudioside A and decreased content of stevioside is the main concern lately. This is due to rebaudioside A having a more desirable sweet flavour taste than stevioside which possesses bitter aftertaste. In respect to that many biotechnological approaches are being used for the industrial improvement and manipulation of steviol glycosides content of Stevia rebaudiana. Transcriptome profiling has emerged as a useful tool to identify target genes involved in the steviol glycosides biosynthesis pathway. Understanding the mechanism and biosynthesis pathway of these compounds has further helped to improve the glycosides profile by up-regulating and down-regulating the desired genes. The aim of this paper is to describe the latest development in the transcriptome profiling in Stevia rebaudiana as well as to discuss the methods used in this endeavour.